Dose reduction of docetaxel avoids the usage of pegfilgrastim in docetaxel plus ramucirumab therapy for recurrent nonsmall cell lung cancer - Kosuke Hamai; Shinya Miyaka; Shinpei Tada; Suguru Fujita; Tetsu Hirakawa; Mirai Matsumura; Sayaka Ueno; Takuya Tanimoto; Nobuhisa Ishikawa (Cancer Reports, 2023)
Abstract Background Pegfilgrastim is recommended in docetaxel plus ramucirumab (DTX + RAM) therapy for recurrent nonsmall cell lung cancer (NSCLC) because of the associated frequency of febrile neutropenia (FN). However, the FN occurs less frequently when the dose of DTX is reduced because of other adverse events, such as appetite loss and oral mucositis. Methods and Results Twenty‐two patients with recurrent NSCLC who received DTX + RAM therapy at the Hiroshima Prefectural Hospital. The cut‐off value which is the most unlikely to cause FN without the combined use of pegfilgrastim was set using a receiver operating characteristic (ROC) curve. This was created according to the dose of DTX and the presence or absence of the onset of FN. We compared the incidence of FN when a DTX dose above and below the cut‐off value was used. The ROC curve showed that 48 mg/m2 was the best cut‐off value that predicted whether FN was likely to occur when pegfilgrastim was not used concurrently. The incidence of FN was 26.1% for DTX ≥48 mg/m2 and 5.1% for DTX <48 mg/m2. Conclusions Pegfilgrastim can be discontinued when the dose of DTX is reduced to <48 mg/m2 due to nonhematological toxicities.